Water When It Counts : Reducing Scarcity through Irrigation Monitoring in Central Mozambique - Christian, Paul; Kondylis, Florence; Mueller, Valerie; Zwager, Astrid; Siegfried, Tobias (World Bank, Washington, DC, 2018)
Management of common-pool resources in the absence of individual pricing can lead to suboptimal allocation. In the context of irrigation schemes, this can create water scarcity even when there is sufficient water to meet the total requirements. High-frequency data from three irrigation schemes in Mozambique reveal patterns consistent with inefficiency in allocations. A randomized control trial compares two feedback tools: i) general information, charting the water requirements for common crops, and ii) individualized information, comparing water requirements with each farmer's water use in the same season of the previous year. Both types of feedback tools lead to higher reported and observed sufficiency of water relative to recommendations, and nearly eliminate reports of conflicts over water. The experiment fails to detect an additional effect of individualized comparative feedback relative to a general information treatment.